2016
DOI: 10.18632/oncotarget.9679
|View full text |Cite
|
Sign up to set email alerts
|

FERMT2 rs17125944 polymorphism with Alzheimer's disease risk: a replication and meta-analysis

Abstract: A recent meta-analysis of genome-wide association studies (GWAS) in population of Caucasian identified a single nucleotide polymorphism (SNP) rs17125944 in the FERMT2 gene as a new susceptibility locus for late-onset Alzheimer's disease (LOAD). In order to validate the association of the rs17125944 polymorphism with LOAD risk in the northern Han Chinese, we recruited a case–control study of 2338 Han Chinese subjects (984 cases and 1354 age- and gender-matched controls). Our results demonstrated that there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A meta-analysis of GWAS in individuals of European ancestry identified rs17125944 of FERMT2 as a risk factor for LOAD, even though this was inconsistent in different ethnic groups (Lambert et al, 2013). Zhang et al (2016) could not corroborate this association in the northern Han Chinese population. No studies have yet been conducted to assess the relationship between SNP rs17125924 within the FERMT2 gene and AD susceptibility in the Asian population.…”
Section: Discussionmentioning
confidence: 95%
“…A meta-analysis of GWAS in individuals of European ancestry identified rs17125944 of FERMT2 as a risk factor for LOAD, even though this was inconsistent in different ethnic groups (Lambert et al, 2013). Zhang et al (2016) could not corroborate this association in the northern Han Chinese population. No studies have yet been conducted to assess the relationship between SNP rs17125924 within the FERMT2 gene and AD susceptibility in the Asian population.…”
Section: Discussionmentioning
confidence: 95%
“…Besides the most consistent genetic risk factor ApoE for Sporadic AD, some studies have also reported many genetic risk factors that appear distinct AD susceptibility between Caucasian and East Asian populations. For instance, following genes were proven to be only associated with AD risk in Caucasian populations but not in East Asian populations: Triggering Receptor Expressed On Myeloid Cells 2 (TREM2) [44, 45], Solute Carrier Family 24 Member 4 (SLC24A4) [46], NME/NM23 Family Member 8 (NME8) [47], GRB2 Associated Binding Protein 2 (GAB2) [48], Myocyte Enhancer Factor 2C (MEF2C) [49], Inositol Polyphosphate-5-Phosphatase D (INPP5D) [50], CLU [51], ABCA7, CD2AP, and EPHA1 [25], Fermitin Family Member 2 (FERMT2) [52]. Hence, the complex difference among different ethnicities and races probably cause the genetic heterogeneity of AD between Caucasians and East Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale genome-wide association studies (GWASs) have identified several novel genetic risk loci in European population, and candidate gene studies have replicated these findings in other populations (Liu et al, 2012; Liu et al, 2013b; Liu et al, 2013c; Liu et al, 2013d; Liu et al, 2014a; Liu et al, 2014b; Liu et al, 2014c; Chen et al, 2015; Li et al, 2015; Shen et al, 2015; Zhang et al, 2015; Chang et al, 2016; Li et al, 2016; Liu and Jiang, 2016; Liu et al, 2016; Ma et al, 2016; Tan et al, 2016; Zhang et al, 2016b). Whole-genome sequencing has highlighted the role of TREM2 in AD (Jiang et al, 2016; Zhang et al, 2016a; Ulland and Colonna, 2018). However, these AD susceptibility loci could only explain 28.57% AD genetic risk (Cuyvers and Sleegers, 2016).…”
Section: Introductionmentioning
confidence: 99%